REVITALIZATION OF TV AND VIDEO IN THE PERIOD OF «STAGNATION» AS ONE OF THE FACTORS REDUCING KINODOCUMENT - M. Kosinova (Вестник университета)
The article discusses the process of expanding the scope of television production and, later, video, and, as a consequence of this process, the fall of kinodocument in the era of Stagnation. While the quality of television films in the 1970s, has grown, the quality of films has steadily declined. In this regard, the audience gradually refocused his attention from the big screen to television. In the 1970s movie sociology had been intensified. Sociologists tried unsuccessfully to solve the problem of the fall of kinodocument. Soon the cinema have got another competitor - video. This further exacerbated the problems of the movie. Income from box office had been steadily declining, reaching a critical minimum, on the eve of restructuring.